2019
DOI: 10.3390/educsci9010030
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Engineering Role-Play to Teach Systems Engineering Methods

Abstract: Students engaged in systems engineering education typically lack experience and understanding of the multidisciplinary complexity of systems engineering projects. Consequently, students struggle to understand the value, rationale, and usefulness of established systems engineering methods, often perceiving them as banal or trivial. The paper presents a learning activity based on a three-stage reverse engineering role-play developed to increase students’ awareness of the importance of correctly using systems eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Lastly, the evaluation of soft skills acquired by the students during the activity showed that problem solving, collaboration, and communication are the most acquired skills. Our results in soft skills evaluation confirm those of [6,9,27,47] that developed RE tools and pedagogies in the educational field. Specifically, they show considerable strengths in hands‐on capability, creativity, and problem solving.…”
Section: Discussion and Limits Of The Studysupporting
confidence: 86%
“…Lastly, the evaluation of soft skills acquired by the students during the activity showed that problem solving, collaboration, and communication are the most acquired skills. Our results in soft skills evaluation confirm those of [6,9,27,47] that developed RE tools and pedagogies in the educational field. Specifically, they show considerable strengths in hands‐on capability, creativity, and problem solving.…”
Section: Discussion and Limits Of The Studysupporting
confidence: 86%
“…First, REP promotes students' understanding of theoretical concepts by actually participating in hands‐on experience [12]. Product dissection greatly helps to enhance concept comprehension and transfer [4]. Research showed that teams that completed dissection present a higher degree of design competency than those in the no‐dissection teams [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many approaches to teach design in engineering education, ranging from more "traditional" approaches focusing on specific modules treating detailed technical features of machine design, to more innovative approaches requiring cross-disciplinary skills in group work, logistics or management. When teaching models for VDD and systems engineering a challenge resides in making the student aware of the "broadness of the system" (Muller and Bonnema 2013), to make them understand the benefits and drawback of such approaches (Bertoni 2019). As highlighted by Muller and Bonnema (2013), systems engineering students might easily perceive the models as "open doors", missing a frame of reference and a background to understand what such models or techniques offer, thus categorizing them more or less as the application of "common sense".…”
Section: The Challenge Of Teaching Value Modeling In Preliminary Designmentioning
confidence: 99%